Versions of Darkness: Dante and Eckhart (A Dialogue). Issue 1 (April 2021) - Kirkpatrick, Robin
Abstract : This paper does not offer an argument. Indeed, without calling into question the validity of traditional modes of theological and academic discussion (as in journal abstracts), these pages suggest that verse might encourage participation in a theological action. A trialogue is offered here in which extracts from Dante and Eckart are interspersed with choric passages reflecting the darkness in which the writer of this paper operates. And the reader is invited to join in the hermeneutic choreography.